Staff or caduceus? Confusing representations in medical symbology - Lazo, Orlando R. (Revista Gregoriana de Ciencias de la Salud, 2024)
The essay "The sacred serpent: a journey to the roots of Medicine" analyzes the historical confusion between the Caduceus of Mercury, a symbol of commerce, and the Rod of Asclepius, the legitimate emblem of medicine. It explains how an error originating in the 16th century, when a German printer used the Caduceus in medical books, led to its erroneous adoption in healthcare contexts. Through a historical and cultural analysis, the article highlights that the Rod of Asclepius, represented by a serpent entwined around a staff, is associated with the Greek demigod Asclepius, linked to healing and regenerative wisdom. The authors delve into the symbolic and semantic differences between the two emblems and critique the distortion of professional medical identity by adopting a commercial symbol. Although the essay rigorously addresses the mythology and cultural roots of these symbols, it identifies as a limitation the lack of discussion on their contemporary implications. In summary, the text emphasizes the importance of preserving historical accuracy in medical symbolism, fostering reflection on the cultural and professional impact of these icons on society’s perception of Medicine.